Identifying Of Student’s Creative Thinking Skill In Fluid Dynamics - Nadia Darma Putri; Arif Hidayat; Supriyono Koes (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Fluid mechanics is studied in many different disciplines. Fluid dynamics as introduced in basic physics includes conservation of momentum or the equation of continuity, Bernoulli’s equation and ideas such as lift and thrus. Fluid dynamics combines concepts from kinematics and dynamics. Studying fluid dynamics requires the ability to connect knowledge from various laws and concepts in physics. The ability to integrate various disciplines in solving a complex problem is needed in this century. Creative thinking skills are needed to analyze problems, predict solutions, and evaluate results. This research aims to determine student’s creative thinking skills in fluid dynamics. The method that used in research is qualitative descriptive. Subjects were choosen by purposive sampling, based on student’s answers. Data collected from fluid dynamics tests and interviews. The result of this study indicates students who have conceptual understanding on fluid dynamics have high fluency and elaborated levels, but for novelty aspect, students must combine the answers with various scientific disciplines such as biology, engineering and mathematics. While students with low fluency levels are caused by misconceptions on fluid dynamics so students are unable to provide detailed explanations of a case and there is no novelty of the solution given.